ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Pratiwi, Aprillia Hanna; Suparman, Tarpan; Prihamdani, Depi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the analysis of the use of digital learning media in mathematics subjects at SDN Karawang Wetan I. The method used in this research is descriptive qualitative with the type of case study research. Data was obtained from class teachers and fourth grade students of SDN Karawang Wetan I. Data collection techniques used in this study were observation, interviews, and documentation. The data obtained was analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the use of canva-based digital media in learning can significantly improve the understanding of mathematics and learning interest of students at the elementary school level.